Determinants Of Accounting Fraud Tendency: The Role Of Religiosity As A Moderating Variable - Naila Hasnindiaz Tiffani; Condro Widodo (Journal of Economic, Bussines and Accounting (COSTING), 2024)
This study was conducted to determine the effect of internal control, integrity, organizational culture on the tendency of accounting fraud with religiosity as a moderating variable. The theory used in this research work is agency theory and Hexagon fraud theory. The population in this study were company employees, using simple random sampling techniques. The sample was taken as many as 102 employees using the Slovin formula. Data collection using the questionnaire method. The results of the study are internal control and organizational culture have a positive and insignificant effect on the tendency of accounting fraud, integrity has a negative and significant effect on the tendency of accounting fraud. Furthermore, religiosity is not able to moderate internal control and integrity on the tendency of accounting fraud, and religiosity weakens organizational culture on the tendency of accounting fraud.